2011
DOI: 10.1016/j.bbamcr.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

PKCθ activation in pancreatic acinar cells by gastrointestinal hormones/neurotransmitters and growth factors is needed for stimulation of numerous important cellular signaling cascades

Abstract: The novel PKCθ isoform is highly expressed in T-cells, brain and skeletal muscle and originally thought to have a restricted distribution. It has been extensively studied in T-cells and shown to be important for apoptosis, T-cell activation and proliferation. Recent studies showed its presence in other tissues and importance in insulin signaling, lung surfactant secretion, intestinal barrier permeability, platelet and mast-cell functions. However, little information is available for PKCθ activation by gastroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…We found that the kinetics of CCK-stimulated PAK2 activation was similar to those observed in pancreatic acini with the SFK, Yes, PKC theta, PYK2 and PKD[41,54,77,94] in that it showed a rapid increase, which subsequently partially decreased(by 40%), but was sustained over time. However, it differed from CCK’s activation of p125 FAK or Lyn[39,78], which after initial stimulation decreases markedly to almost basal levels.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We found that the kinetics of CCK-stimulated PAK2 activation was similar to those observed in pancreatic acini with the SFK, Yes, PKC theta, PYK2 and PKD[41,54,77,94] in that it showed a rapid increase, which subsequently partially decreased(by 40%), but was sustained over time. However, it differed from CCK’s activation of p125 FAK or Lyn[39,78], which after initial stimulation decreases markedly to almost basal levels.…”
Section: Discussionsupporting
confidence: 65%
“…Previous results have demonstrated that numerous GI growth factors (HGF, EGF, bFGF, insulin, IGF and PDGF) are able to interact with specific receptors on pancreatic acinar cells and stimulate growth and/or protein synthesis as well as alter other cellular functions[33,33,54,57,7779]. We observed activation of PAK2 by EGF, bFGF and PDGF, but not by insulin, IGF-1 and HGF.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Additionally, PKCθ is an important signaling molecule in pancreatic acinar cells that can be activated by CCK [30], as evidenced by phosphorylation at amino-acid residue T538 and translocation from the cytosol to the plasma membrane [31]. This activation occurs through the CCK A receptor such that most activation occurs through the low affinity state, but about 30% of the activation occurs through the high affinity receptor state [30].…”
Section: Pkc In Normal Pancreatic Functionsmentioning
confidence: 99%
“…This activation occurs through the CCK A receptor such that most activation occurs through the low affinity state, but about 30% of the activation occurs through the high affinity receptor state [30]. While PKCθ does not affect amylase release, active PKCθ affects many downstream targets including Src, PYK2, and FAK [30]. …”
Section: Pkc In Normal Pancreatic Functionsmentioning
confidence: 99%